∫∫ √[1 - sin²(x + y)] dxdy
= ∫∫ √[cos²(x + y)] dxdy
= ∫∫ |cos(x + y)| dxdy
= ∫(0,π/2) dx [∫(0,π/2 - x) cos(x + y) dx + ∫(π/2 - x,π/2) (- )cos(x + y) dx ]
= ∫(0,π/2) [sin(x + y):(0,π/2 - x)] dx - ∫(0,π/2) [sin(x + y):(π/2 - x,π/2)] dx
= ∫(0,π/2) [sin(x + π/2 - x) - sinx] dx - ∫(0,π/2) [sin(x + π/2) - sin(x + π/2 - x)] dx
= ∫(0,π/2) (1 - sinx) dx - ∫(0,π/2) (cosx - 1) dx
= (x + cosx - sinx + x):(0,π/2)
= (π/2 + 0 - 1 + π/2) - (0 + 1 - 0 + 0)
= π - 2
![](http://g.hiphotos.baidu.com/zhidao/wh%3D600%2C800/sign=0584dbdb0823dd542126af6ee1399fe6/e850352ac65c10389dd4697db3119313b17e89e3.jpg)